Long-Term Survivorship of Cervical Spine Procedures; A Survivorship Meta-Analysis and Meta-Regression. Issue 3 (April 2023) - Sarraj, Mohamed; Hache, Philip; Foroutan, Farid; Oitment, Colby; Marion, Travis E.; Guha, Daipayan; Pahuta, Markian
Study Design: Systematic Review Objectives: To conduct a meta-analysis on the survivorship of commonly performed cervical spine procedures to develop survival function curves for (i) second surgery at any cervical level, and (ii) adjacent level surgery. Methods: A systematic review of was conducted following PRISMA guidelines. Articles with cohorts of greater than 20 patients followed for a minimum of 36 months and with available survival data were included. Procedures included were anterior cervical discectomy and fusion (ACDF), cervical disc arthroplasty (ADR), laminoplasty (LAMP), and posterior laminectomy and fusion (PDIF). Reconstructed individual patient data were pooled across studies using parametric Bayesian survival meta-regression. Results: Of 1829 initial titles, 16 citations were included for analysis. 73 811 patients were included in the second surgery analysis and 2858 patients in the adjacent level surgery analysis. We fit a Log normal accelerated failure time model to the second surgery data and a Gompertz proportional hazards model to the adjacent level surgery data. Relative to ACDF, the risk of second surgery was higher with ADR and PDIF with acceleration factors 1.73 (95% CrI: 1.04, 2.80) and 1.35 (95% CrI: 1.25, 1.46) respectively. Relative to ACDF, the risk of second surgery was lower with LAMP with deceleration factor .06 (95% CrI: .05, .07). ADR decreased the risk of adjacent level surgery with hazard ratio .43 (95% CrI: .33, .55). Conclusions: In cases of clinical equipoise between fusion procedures, our analysis suggests superior survivorship with anterior procedures. For all procedures, laminoplasty demonstrated superior survivorship.